Stereotypes -- funny because they are true | Katerina Vrana | TEDxThessaloniki (TEDxChania, 2012)
: Είμαι η Κατερίνα Βρανά. Είμαι Έλληνας, ζω στην Ελλάδα, ζω στην Λονδίνα. Είμαι κομμεδιότητας. Όσον αφορά το δικαίωμα να δημιουργήσει, είμαι κομμεδιότητας. Έχω δύο αδερφές, ένας είναι 30, ο άλλος 14. Το 30-χρονος είναι δραστηριότητας και φωτογραφός. Είναι δραστηριότητας της τραγούδας που θα κλείσει το TED Thessaloniki, το TEDx. Ο κομμεδιότητας μας είναι η Κατερίνα Βρανά. Είμαι η κομμεδιότητας της τραγούδας που θα κλείσει το TED Thessaloniki, το TEDx. Οι ελληνικοί παρέντες μας είναι πολύ χαρούμενοι στις προορισμούς μας. Θα κάνεις ποτέ χρήματα, όχι. Το 14-χρονος θέλει να είναι αδερφός. Ωχ! Είχε ελπίδα! Και το μυαλό μου είναι σαν αυτό, γιατί είναι αυτό. Δεν υπάρχει συζήτηση. Δεν υπάρχει συζήτηση τόσο πολύ. Είναι μεγάλο, αλλά δεν είναι τόσο εξαιρετικό. Στην Ελλάδα, έχει γίνει ένας εξοπλισμός. Οι άνθρωποι με σταματήσουν στη διάρκεια. Οι άνθρωποι το πιάνουν χωρίς να με ρωτήσουν. Και τότε υπάρχουν αδερφούς που φέρνουν μικρούς παιδιά από τις κλασσίες και πιάνουν, κοίτα, κοίτα τη γυναίκα που είναι σαν ένα τραγούδι. Είναι πολύ αρνητικό. Είμαι στην Ελλάδα για 10 χρόνια. Επίσης, είμαι 100% ελληνική. Ήμουν γενική εδώ. Ήμουν γενική εδώ. Οι παιδιά μου είναι ελληνικοί, η οικογένειά μου εδώ. Δεν έχω κανέναν ιδέα γιατί μιλάω ελληνικά σαν αυτό. Καθόλου κανέναν. Είναι ένας φλούκ. Το άλλο της οικογένειας δεν μιλάει ελληνικά. Μιλάει σαν ελληνικούς ελληνικούς. Ζήτησα τη μητέρα μου. Είπα, πώς μπορείς, όταν μιλάς ελληνικά. Ήμουν όμορφη. Και το άλλο της οικογένειας μιλάει σαν ελληνικούς ελληνικούς. Και η μητέρα μου είπε, «Αχ, μητέρα μου, όταν μιλήσατε, ήσασταν τόσο αγόρας». «Μην κλάψετε αυτό!» «Τοί αγόρας!» Και είπε, «Ο πατέρας και εγώ σκέφτησαμε, ότι αυτό θα χρειάζεται προσωπικότητα, και η λεγότητα βοηθά. Ήθελα φραντινό και πιάνο. Ο πατέρας ήθελε ελληνικό». «Ναι, Κατερίνα. Ήθελα ελληνικό». Αυτός είναι ο πατέρας μου. «Θα σας πω γιατί. Γιατί η ελληνική κυβέρνηση γνωρίζει πολύ αγόρας. Πάτε!» Όχι. Όχι. Ο Βιλιέμ ήθελε να γνωρίζει, και η Χαρή έχει πολύ κόκκινο κόκκινο. Και δεν έχω τίποτα σχετικά με το κόκκινο κόκκινο. Είναι γιατί θα είχα τελικά το σεξ με τη Χαρή. Σε πείτε αυτό τώρα. Δεν θα το έκανα στον ήλιο. Το έκανα στον κόκκινο. Ξέρετε τι σημαίνει. Αν έχεις σεξ με τη Χαρή στον ήλιο, θα εξελίξει. Δεν είναι μια καλή ιδέα. Έχω ζήσει στην Λονδία, όπως είπα, για περίπου μια δεκαετία. Αυτό που συνέβη είναι ότι, εκεί, νιώθω πραγματικά ελληνικός. Αλλά όταν έρθω σπίτι, υπάρχει μια αλλαγή στην ιδέα μου. Και σύντομα βρίσκω να πω, πως οι Ελληνικοί δημιουργούνται σύντομα. Θεέ μου. Υποθέτω να διαβάζω να μην αισθάνομαι ελληνικός στις δύο χώρες. Αλλά ένα από τα πράγματα που έρχομαι να βοηθήσω για την Ελληνική, για παράδειγμα, είναι το πώς έρχονται αγόρα. Δεν το κάνουν. Όταν ένας Ελληνικός άνθρωπος έρχεται αγόρας, γράψουν σε ένα σημαντικό γραμμό. Υποθέτω να πω, πως είναι το πιο αγόρα. Ένας ελληνικός φίλος μου ήταν σε ένα τρένο. Το τρένο σταματήθηκε μέσα από δύο χώρες. Και τους έφεραν εκεί για έναν ώρα και μήνα. Δεν πήραν πως. Απλογιστήθηκαν. Οι φίλοι μου είπαν, Κατερίνα, είχα τόσο αγόρα, είχα τόσο αγόρα, είχα τόσο αγόρα, και με amounts Early Share. Είπα, κατερίνα. Δεν πήραν πο tweaks. over number three. Μ explored Ghillieistic And I was really surprised. At first, I thought, droppedmiyor, It was like, You better keep out before you dive to me. You better keep out because you don't know what planet or whato you are going on. What? What? You keep us here like animals, like animals! You call this a European country, this is not Europe, I don't understand. Wait, there's so much more. And then someone always goes, where is the manager? I want to speak to the manager, please sir, please sir, sit down, you're becoming hysterical. Who are you to tell me what to do, eh? Who are you? Screw you! I screw your mother! Wow! It takes five seconds to escalate to that level. And also, as far as that goes, right, that I screw your mother, it makes no sense. Like what? I screw your mother? No, really? What a coincidence! Of all the boats in all of Attiki, you walk into mine. The son of whose mother you are screwing. Hello, Yannis, the son. The lady who you're having carnal relations with. What a... so pleasant. This kind of... also, right, no one you ever want to say it to you ever does, right? Because if Bill Gates comes up to me and goes, I screw your mother, I'll be like, Daddy! You're home! And we'll all be going to Cannes on my jet. So I wish the Greeks would kind of temper their rage, that immediate... that kind of happens. I don't expect them to become like the English, no, dear sir, I regret to inform, I screw your mother. Just a bit more of a thing. Also, the other thing I've come to really enjoy about the UK, and I know this is weird for a Greek person, is the weather. I know, I know, I know, I know. Thank you... ooh, one person going, yes! You tell them it rains! The thing is, like, I keep trying to explain to the British that everywhere else in the world, clouds are functional rather than an aesthetic choice. Like in the UK, the clouds arrive and just go, hi, we're here. We're just going to sit here, maybe a bit lower, do nothing, hi. Like in other countries, when the clouds arrive, it's going to rain, and the heavens open, water pours down, water so thick you cannot see through it, so it's like, where is my tzatziki? Behind the rain, who knows? That lasts for two hours, then it stops, the sun comes out and we forget about it. In the UK, the same amount of water takes 24 hours to come down. Because in the UK, rain is that really soft mist, right? It's like a cat spraying your tent to show its territory, do you know what I mean? It's a very gentle thing. It's a tippy-tap, it's called drizzle, and that's what I've come to love, because drizzle is rain being quintessentially British, right? It's rain going, I'm terribly sorry, I'm coming down, I don't mean to be in the way, I'm just going to come around you, I won't get anyone wet, I promise, just pretend I'm not here, but I'm going to be absolutely fine. No, no, everyone's going to know I'm here, you're not here. Did I get you wet? How clumsy of me, I do apologise, I didn't mean to do that, I'm just going to come over here, I'm going to be gone in five minutes, I promise, I'm so sorry. I do apologise, 24 hours and I'm still here, it's getting awkward now, isn't it, I'm so sorry. I don't mean to be doing this, I'm going to be really genuine, I'm so sorry, I really don't, I'm just going to, I'm the Hugh Grant of moisture. And my hair absorbs moisture, so whenever it drizzles my hair goes, and a mile radius around me stays completely dry, and I look like I've got all of the Jackson 4 on my head, because he's dead. Now, the thing is that I'm in the UK, well I went to the UK to act, and that's when I discovered that I'm not Greek enough, because I used to be sent up for auditions for Greek and Mediterranean parts, only to be told that I don't look Greek enough. I'll translate that for you, it means I don't have a mono-brow and a moustache, because Irini Papa has cast a very long shadow. So I usually got feedback of the kind, you know, we're looking for someone who looks like Salma Hayek, she's Mexican. So I went up for casting for the movie Troy, do we remember? The movie Troy, yeah. So I went up for one of the small parts, one of the slave girls that had only one line, and my line was, more chicken my lord. And I did that really well. I ended up in the final five, and they line us up, and the casting director comes in and goes, oh no, no, no, you're too fair to be Greek. I said, who, what now? You're too fair to be Greek. I was like, I'm too fair to be Greek. I'm the only Greek in the room. I'm too fair to be Greek, in a movie where the Greek warrior Achilles is played by Brad friggin' Pitt. I'm too fair to be Greek. I didn't get the part. An Albanian girl got it. Go over there, take our jobs. Where's Kaplani? But even acting and comedy are just steps for my final, because my 12-step plan for global domination. I'll find a pose. It'll be better than this, I promise. Because I think I'm Greek. We did it before, I can do it again, bring it on. I think the world will be a lovely place if everyone listens to me. It's going to be a little bit like Hitler, with less genocide, more hair, and really good shoes. So more like Dubai. I'm going to wear a crown and a robe. I'm going to tell people what to do, and they will do it. It's going to be lovely. I've recently realized I'm probably going to end up looking like a kindergarten teacher, trying to manage an unruly classroom. So I'm going to turn up in a crown and a robe, looking a bit stupid, making grandiose announcements like, Hello, I am Katerina Vrana. Hello, I'm going to be your global dominator for the foreseeable future. Please lay all gifts by my... What is it, Thailand? Yes, Thailand, you may massage my feet. Israel, Palestine, be quiet. Somalia, darling, why are you dressed as a pirate? No, that's slightly inappropriate. Well done, America. Everyone, America has done a drawing. Yes, dear. No, we can all see. Yes, the black man is in the White House. Yay. And he's still alive. Hasn't America done well, everyone? It's very good. Now, darling, stop drawing and look to your sums, because the numbers are all wrong. And stop copying from America. You're old enough to know better. Greece, you're making me look really bad. No, Palestine, I don't care who started it. Israel, give Palestine her Gaza back now. The two of you learn to share. Iran, put the stone down. No, my love, that's not democracy. No, dear, I know. I'm Greek. I gave it to you. Bloody Persian. And what's that in your mouth? Spit it out. Spit it. Spit it. Who gave uranium to Iran? You know they don't know what to do with it. I just, I don't... Okay, Italy. Italy, tell your dad to stop playing with the little girls in the class. What's that? Cyprus, I don't understand what you're saying. Say it again. Slower. 12 points to Greece. That's really going to help everyone. Don't clap. Israel, just because your book says so, does not make it right. Okay, Palestine, why did you just blow up in Israel's face? What do you mean? Because Syria told you to. And if Syria told you to jump off a cliff, would you, Palestine, get off the cliff? The two of you play nicely together or I'm sending you to the corner with North Korea. Am I making myself clear? Greece, stop calling Germany's mother a whore. And India, get off the phone. Why can't you all be more like Canada? They do gall. They're very good. Actually, it's exhausting just performing this. I don't think I'm ever going to make it to global domination. I'm probably just going to sit at home reading gossip magazines. You know, the ones full of celebrities and cellulite. It's the way to go. I just want to tell you one more thing before I head off. What I found was the biggest difference between Greeks and the British, as I like to call them, is their approach towards the opposite sex. When I first went over there, I thought there was something wrong with me because no one stared at me intently for hours. Because you know how the Greeks sit in cafes and this is how they watch women go by. In the UK, this is how they watch women. Don't look, it's inappropriate. And also in Greece, you walk down the street and people shout random, slightly complimentary things at you. I was walking down one of the main streets in Athens and a car went by honked and shouted, you make the pavement Greek, my nanny. I was like, did he call me fat? In the UK, the only people who shout anything like that are the builders. And they only ever shout things like, show us your tits. No one ever has. I don't know why they keep insisting. You get other things shouted at you in the UK, like painfully obvious things. I walk down the street and people shout to me, oy, you've got big hair. I'm like, yes, I know. I have a mirror and no peripheral vision. I'm like those horses that draw the carts. I have natural blinders. If you want to attack me, do it from the side. I won't see you coming. This is what a Greek cab driver just showed me the biggest difference between oy, you've got big hair, and then I get into this Greek cab now a week ago because I came over to vote. That went well. It was nine degrees in the UK and I come here and it was 29. I get into this taxi and I go, oh, God, it's so hot. I'm sweating so much. Without pause, the Greek cab driver went, your sweat is very lucky to be traveling down your body. Thank you very much. Bye.